Pembangkitan Massa Medan Skalar dan Boson Tera pada Model Simetri Kiri Kanan Termodifikasi Berdasarkan Grup Tera SU(3)_C⊗SU(2)_L⊗SU(2)_R⊗U(1)_Y - Istikomah, Istikomah Istikomah (Universitas Negeri Semarang, 2020)
Modified Left-Right Symmetry Model has been constructed based on the gauge group . In this model there is a left sector consisting of Standard Model particles with the addition of right-handed neutrino and the doublet scalar , while the particle pairs are in the right sector. In addition, also added scalar fields and which can be intermediaries of interaction between the two sectors. Scalar fields masses can be generated via scalar potensial with the result that . Whereas the mass of charged gauge bosons , the masses of neutral gauge bosons masses and the mass of photon is zero.